#TITLE_ALTERNATIVE# - (S2-818227), SUWADJI
This study is concerned with the use of Asbuton as a binder in road base materials using the hot mix method. The objective of the investigation was to determine the extent to which road base material incorporating Asbuton met the Bina Marga specifications for bitumen-bound base material prepared in a hot mix process. Aspects of the specification investigated were aggregate gradation and traffic category. The mix characteristics investigated were the Marshall parameters and resistance to the effect of water, as determined by unconfined compressive strength tests. The results show that aggregate of Bina Marga Type II gradation mixed with Asbuton in the amount required to produce a bitumen content of 7-8 percent forms a mixture which meets the specification for road base material for use in medium traffic conditions only. Retained compressive strength of Asbuton treated base material, following standard conditioning procedures (i.e. immersion in water for 24 hours at 60oC or for 96 hours at 49oC) is very low. Substantial improvement results if 2 % hydrated lime is added to the mix. Also, as might be expected, reduced severity of conditioning results in an improvement. No conclusions can be drawn regarding level of severity of conditioning appropriate to Indonesian conditions.